PENGARUH ACADEMIC SELF-EFFICACY TERHADAP PROKRASTINASI AKADEMIK MAHASISWA - Ian Wahyu Saputra; Sutarto Wijono (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
This study aims to determine whether there is an influenceAcademic Self-Efficacy on academic procrastination in students. The type of research used is a quantitative method with a simple linear regression design. Participants involved in this study were 135 students of the Faculty of Psychology, class of 2022. The measurement scale used was The Academic Self-Efficacy Scale (TASES) and academic procrastination scale. Based on the results of the simple linear regression test, the t-test was obtained = 10.748 (> 1.978); p = 0.000 (p ≤ 0.05) and the R Square= 0.465. Based on the results of this study, it can be concluded that there is a significant influence Academic Self-Efficacy on Academic Procrastination in Faculty of Psychology students class of 2022. Thus, the research hypothesis proposed in this study can be accepted. The results of this study can help individuals to realize that academic procrastination in students can be controlled by increasing Academic Self-Efficacy. Increase Academic Self-Efficacy can be one of the factors that can control individuals not to delay in completing academic tasks which will bring many negative impacts to the individual himself. The results of this study indicate that the higher Academic Self-Efficacy then it will reduce the potential for academic procrastination behavior in students.